LANDSLIDE MONITORING IN TECTONICALLY ACTIVE REGIONS WITH REFERENCE TO KAMCHATKA - Betelev N.P.; Guzeev E.A.; Delemen I.F.; Kulachkin B.I.; Piradov K.A.; Radkevich A.I.; Utkin I.S. (My University, 2001)
Landslide processes are actively stimulated in Kamchatka by atmospheric phenomena (typhoons and cyclones) and also by seismic and volcanic events. A complex of methods is offered here for investigating landslide processes using measurements of nonstationary thermal and dynamic (strength, structural, and hydraulic) fields, including a method of static testing developed by the authors and other methods. Landslide monitoring is included into a complex of methods used to monitor the behavior of natural systems.